Personality Characteristics and Social Media Use - Gountas, Sandra; Gountas, J. (Routledge, 2012)
Research indicates that narcissism and the desire for fame are increasing amongst young people, which is of concern to many researchers (Ryan and Xenos,2011; Twenge, Konrath, Foster, Campbell and Bushman, 2008). At the same time, social media usage is increasing and there is concern that the two may be related (Bergman, Fearrington, Davenport and Bergman, 2011). On the positive side, social media have many uses that are not linked solely to individuals’ self-presentation and communications for example; social networking sites are used as a platform in the education delivery mix in many institutions, in commercial advertising, and as social marketing forums. Studies indicate that different people have different motivations and benefits from participation in social networking sites (Park, Fee, Valenzuela, 2009; Ellison, Steinfield and Lampe, 2007). However, there is still a paucity of research concerned with the relationship between individual differences and social networking(Muscanell and Guadagno, 2012). This paper explores the associations between individual characteristics and social media use.